2022
DOI: 10.3390/jpm12071148
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Acute Aortic Dissection

Abstract: Cardiovascular disease (CVD) represents the most important cause of mortality and morbidity worldwide. There is heterogeneity in the epidemiology and management of CVD between male and female patients. In the specific case of acute aortic dissection (AAD), women, at the time of diagnosis, are older than men and complain less frequently of an abrupt onset of pain with delayed presentation to the emergency department. Furthermore, a history of hypertension and chronic obstructive pulmonary disease is more common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
(92 reference statements)
2
9
0
1
Order By: Relevance
“…Women were less frequently affected by type ATAAD than men. On the other hand, women tend to be older than men at the time of diagnosis [26]. This is similar to the characteristics of HAD, and further research focusing on gender differences is needed.…”
Section: Factors Associated With Hadmentioning
confidence: 80%
“…Women were less frequently affected by type ATAAD than men. On the other hand, women tend to be older than men at the time of diagnosis [26]. This is similar to the characteristics of HAD, and further research focusing on gender differences is needed.…”
Section: Factors Associated With Hadmentioning
confidence: 80%
“…The results indicated that the studied population's average age was high and that there was a significant level of individual age variability. Multiple factors, including genetics, lifestyle, and overall health, could be responsible for the age range level [30].…”
Section: Discussionmentioning
confidence: 99%
“…18 Recent population-based registries also reported a male predominance in both subtypes. 19 However, 2 previous reports from Japan indicated that the proportion of women was higher among patients with type A-AAD compared with those with type B-AAD. 17, 20 Goda et al surveyed the differences in the characteristics of patients with type A-AAD between Belgian and Japanese centers, and reported that Japanese women were more likely to develop type A-AAD than Belgian women.…”
Section: Disclosuresmentioning
confidence: 91%